Designing a mobile health intervention for preterm home care: Application of conceptual framework. Issue 1 (10th December 2021) - Phagdol, Tenzin; Nayak, Baby S; Lewis, Leslie Edward; Margaret, Binu; George, Anice
Abstract: Mobile health (mHealth) solutions are being widely explored in low‐ and middle‐income countries (LMICs) due to its scope in reducing the healthcare access gap and improving health outcomes. The fit of mHealth solutions to specific users and their viability in a particular setting plays a significant role in the successful adoption and sustainable implementation. This article describes the process of designing a sustainable mHealth application for delivering preterm home care to babies discharged from the neonatal intensive care unit (NICU) in India. Intended end‐users are the parents, who are primary caregivers at home, especially mothers of preterm babies and healthcare providers who cared for them at the hospital. This mHealth application is designed to facilitate continuity of care for these preterm babies transitioning from an intensive healthcare setting to home with unique and complex health care needs. It is equipped to remotely monitor the growth and development for early detection of growth impairment and developmental delay often seen in preterm babies in their early years. Therefore, a mHealth application was designed applying a relevant conceptual framework for successful adoption and an ecological model for sustainability in the Indian setting.